Using the Arau Model to locate groundwater potential zones in the northern regions of Malaysia / Ahmad Kamal Mad Issa et al. - Md. Issa, Ahmad Kamal; Mat Arof, Zakaria; Yahaya, Ahmad Nadzari; Wan Yusof, Kamaruzaman; Mohamad Ibrahim, Norlia; Salleh, M. S. (Universiti Teknologi MARA, Perlis, 2012)
A major portion of water demand in most states in Malaysia is being supplied from surface water sources. These sources are deemed inadequate to fulfil the water demand for the future. Water supply for Perlis which is situated in northern Malaysia is mainly supplied from surface waters with groundwater supplementing this supply for localised use. In this study using an integration of remote sensing and Geographic Information System (GIS) techniques, groundwater potential zones were positively identified resulting in significant savings of resources. The Weighted Linear Combination (WLC) Method in GIS was used to predict potential groundwater zones in the study area based on a new mathematical model. This model called the Arau Equation for Groundwater Potential was applied where six parameters were identified based on Civil Engineering principles. This study investigated the analysis using GIS of landuse produced from a SPOT remote sensing image of Perlis, together with secondary data which consisted of geology, topography elevation, slope distribution, drainage distribution and rainfall distribution data. These data were analyzed to produce thematic maps. In the final analysis specific areas were identified as zones of very high, high, moderate or low in terms of groundwater yield. A reliability of 79% was achieved using the Reliability Analysis when compared to historical data on groundwater boreholes and tubewells in the study area.